Preservative effect of cinnamon Cinnamomun burmannii (Nees & T. nees) blume bark powder on fresh palm oil decanter meal for goats - H. Kusairi, M. Afdal (2013)
Palm oil decanter meal (PODM) is a by-product from the palm oil industry. It is abundantly available and to a limited extent, utilized as organic fertilizer. This by-product has the potential as animal feed due to its high protein content, which is comparable to that of grass. However, the problem of rancidity remained the main constraint in its application as animal feed. Rancidity deteriorates the PODM quality within few days in open air. Antioxidants have been widely applied to preserve food and processed products. Cinnamon (Cinnamomum burmannii) bark (CB) was chosen as a source of antioxidants, as it is cheap and easily available. Hence, the main objective of this study was to preserve PODM quality by inhibiting rancidity using CB. Experiments conducted include determination of the chemical characteristics, rancidity properties and inherent microbial species of PODM; evaluation of different solvents to extract the bioactive compounds present in CB for PODM treatment; palatability test in goats fed treated PODM with ground CB (GCB); in sacco degradability and digestibility of treated PODM with GCB in goats and fermentation kinetics of treated PODM by rumen microbes in vitro. The results showed that fresh PODM contained 267±7.6 g/kg (dry matter), 60±3.6 g/kg (ash), 117±2.1 g/kg (crude protein), 28±5.7 g/kg (ether extract), 751±24.8 g/kg (neutral detergent fibre) and 445±56.6 g/kg (acid detergent fibre). The mineral composition consisted of 0.24±0.08 ppm (Cr), 13.10±0.70 ppm (Fe), 0.43±0.03 ppm (Mn), 0.96±0.02 ppm (Ni), and 6.54±2.19 ppm (Cu). The fatty acid (FA) composition included 40.7±0.84 % (palmitic (C16:0)), 5.6±0.49 % (stearic (C18:0)), 41.2±0.43 % (oleic (C18:1)), 11.0±0.27 % (linoleic (C18:2)) and 1.3±0.50 % (α-linolenic (C18:3)). The rancidity status of fresh PODM measured by peroxide value (PV) and thiobarbituric acids (TBA) values (1.92±0.09 meq/kg and 1.75±0.62 mg/kg, respectively) was low. However, PV and TBA values increased to 18.12 meq/kg and 8.13 mg/kg PODM, respectively within 10 days in the open air. Eight bacterial isolates were obtained, but only four could be identified as it was needed other method to do. They were Kocuria sp Bacillus subtillis, Bacillus megaterium and Paenibacillus nanensis. Three fungal isolates were obtained, but were not identified yet and kept left at the plant protection laboratory. The highest total phenolics and flavonoids were observed in the methanol extract with the values of 111.43 and 286.27 mg gallic acid equivalent/g dry weight (DW), respectively, while the lowest amounts detected in hexane were 57.23 and 64.73 mg gallic acid equivalent/g DW, respectively. Methanol extracts also showed significantly (P<0.05) higher antioxidant activity measured by the 1.1-diphenyl-2-picrylhydrazyl(DPPH) radical scavenging method. The highest value of DPPH inhibition was 69.6±0.24% to scavenge free radical ion. This inhibition was higher than vitamin E (25.4±0.25%) but lower than butylated hydroxytoluene (BHT) (91.8±0.02%).Different levels of CB extract (CBE) and ground CB (GCB) were tested for their effects on PV and TBA of PODM. Both PV and TBA values of PODM were significantly (P<0.05) different among all treatments and over time of sampling. The GCB at 0.1 % (w/w) showed the best reduction in rancidity of PODM with PV and TBA of 10.24 meq/kg and 5.81 mg/kg respectively. Further studies showed that PV and TBA values of PODM were significantly (P<0.05) different among different levels of GCB. The level of 0.2 % of GCB showed the highest reduction in PV and TBA values at 8.96 meq/kg and 4.95 mg/kg respectively. This reduced PV by 42.8 % and TBA by 55.1%. A palatability study was conducted according to the cafeteria method using 4 Kacang Boer crossed goats. The intake of PODM preserved with 0.2% GCB (GDM), untreated PODM (UDM), Napier grass (NG) and Rice straw (RS) as standards was significantly different (P<0.05) on day one and in periods 1, 2 and 3. In period one, intake of GDM, UDM and NG were higher than that of RS. Intake of UDM (362.74 UDM g/day) was higher than that of GDM (211.16 GDM g/day). However, in periods 2 and 3, intake of GDM was significantly (P<0.05) higher than that of UDM. There was no significant difference on the effect of different levels of GDM in the four experimental diets of goats on the total dry matter intake (DMI), the apparent digestibility of DM, neutral detergent fibre (NDF), and acid detergent fibre (ADF). There was no significant difference in rumen pH of goats among treatments. Rumen pH decreased slightly at 2 h and after that increased until 6 h. Rumen pH for all treatments was within the range of 6.47 - 7.10. There were no significant effects of experimental diets on the concentration of ammonia nitrogen (13.20 – 16.68 mg/100ml) in rumen of goats. The nitrogen intake was comparable among four dietary treatments. The effect of experimental diet was significantly different (P<0.05) on faecal N as percentage of intake and faecal N per metabolic weight (mg/kgBW0.75). The effects of diets were not significant in urinary N excretion. However, the effects of experimental diets were significantly different (P<0.05) on N absorption (g/d), N retention (g/d), N retention as percentage of intake (% of intake) and N retention as percentage of absorption of goats. In the fermentation kinetics study in vitro, there was a significant difference (P<0.05) on the effect of experimental diets on a, b and a+b values except for c value. A significant difference (P<0.05) was also observed in gas production at 24, 48 and 96 h. There was not significantly different (P>0.05) in fermentation kinetics between GDM and UDM. The present study showed that methanol was the best solvent to extract CB with high DPPH scavenging activity, but its ability to reduce PV and TBA of PODM was lower than GCB. It was observed that GCB at 0.2 % (w/w) could reduce PV and TBA up to 42.8% and 55.1%, respectively. The GDM was more palatable than UDM after 5 days of experiment and the digestibility of GDM in diet was not significantly different in comparison with the control. It could be concluded that PODM treated with 0.2% of GCB could be used as goat feed without any negative effect on the digestibility of feed and the rumen environment.